2002
DOI: 10.1080/10611860290022688
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Enhancing Effect of Labrasol on the Intestinal Absorption of Insulin in Rats

Abstract: The oral absorption enhancing effect of Labrasol has been studied in rats using insulin as a model peptide/protein drug. Insulin solution was prepared by dissolving insulin in pH 7.4 buffer followed by the addition of Labrasol. The insulin concentration was 50.0 IU/ml. The test insulin/Labrasol solution was administered to the jejunum, ileum and ascending colon of rats at 10.0 IU/kg. After administration, blood samples were collected for 5 h and serum glucose levels and insulin levels were measured. In another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…It implies that magnesium stearate potentiated the mucoadhesiveness of insulin-loaded Eudragit Õ entrapped microspheres in SIF. The high percentage mucoadhesion of the different batches of the microspheres in SIF signifies high mucoadhesive property in intestinal condition where insulin absorption takes place (Yamamoto et al, 1994;Chetty & Chien, 1998;Rosenstock, 2001;Dorkoosh, 2002;Eaimtrakarn et al, 2002;Cefalu, 2004;Chung, 2004;Attivi, 2005;DeFronzo et al, 2005;Ahmed & Goldstein, 2006;Chalasani, 2007;Cui, 2007;Damage et al, 2007;Evans et al, 2011;Akhter & Nijhu, 2012). This shows that the insulin-loaded microspheres will have a prolonged release and thereby enhance bioavailability of insulin, consistent with previous reports (Rosa et al, 2000;Jain et al, 2005;Builders et al, 2008a).…”
Section: Loading Efficiencysupporting
confidence: 79%
See 1 more Smart Citation
“…It implies that magnesium stearate potentiated the mucoadhesiveness of insulin-loaded Eudragit Õ entrapped microspheres in SIF. The high percentage mucoadhesion of the different batches of the microspheres in SIF signifies high mucoadhesive property in intestinal condition where insulin absorption takes place (Yamamoto et al, 1994;Chetty & Chien, 1998;Rosenstock, 2001;Dorkoosh, 2002;Eaimtrakarn et al, 2002;Cefalu, 2004;Chung, 2004;Attivi, 2005;DeFronzo et al, 2005;Ahmed & Goldstein, 2006;Chalasani, 2007;Cui, 2007;Damage et al, 2007;Evans et al, 2011;Akhter & Nijhu, 2012). This shows that the insulin-loaded microspheres will have a prolonged release and thereby enhance bioavailability of insulin, consistent with previous reports (Rosa et al, 2000;Jain et al, 2005;Builders et al, 2008a).…”
Section: Loading Efficiencysupporting
confidence: 79%
“…Various approaches that could be adopted include modification of physicochemical properties such as lipophilicity and enzyme susceptibility, addition of novel function to macromolecules as well as the use of improved carrier system. In other words, methods like protecting insulin from enzymatic degradation, use of penetration enhancers, chemical modification, bioadhesive delivery system, as well as use of carrier systems could help to improve bioavailability of insulin (Heinemann et al, 2001;Rosenstock, 2001;Dorkoosh, 2002;Eaimtrakarn et al, 2002;Heinemann, 2002;Cefalu, 2004;Chung, 2004;Attivi, 2005;DeFronzo et al, 2005;Jain et al, 2005;Kavimandan, 2006;Chalasani, 2007;Cui, 2007;Damge et al, 2007;Ichikawa & Fukumori, 2007). The successful production of an effective oral insulin formulation will depend on the development of an appropriate drug delivery (carrier) system that will protect insulin from the degradative effect of enzymes and pH of the GIT (Caliceti & Veronese, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed to increases the oral bioavailability of insulin including the inhibition of proteolytic enzymes (Ziv et al, 1987;Liu et al, 2003) and use of penetration enhancers (Soltero & Ekwuribe, 2001;Eaimtrakarn et al, 2002;Li & Deng, 2004;Liang & Yang 2005). The use of enzyme inhibitors in long-term therapy however remains questionable because of possible absorption of unwanted proteins, disturbance of digestion of nutritive proteins and stimulation of protease secretion (Shah et al, 2002;Soares et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that Labrasol had a strong absorption enhancing effect and that intestinal absorption of various poorly absorbable drugs including gentamicin, insulin and vancomycin was enhanced in its presence. [18][19][20] However, few studies examined the effect of Labrasol on the function of P-gp in the intestine and the intestinal absorption of P-gp substrates. Cornaire et al (2004) examined the effect of Labrasol on the transport of digoxin by an in vitro everted sac experiment, and reported that 0.5% Labrasol increased the transport of digoxin in this experiment.…”
mentioning
confidence: 99%